A TeamSTEPPS® implementation plan for recently assigned interns and nurses. Issue 6 (2nd November 2019) - Clapper, Timothy C.; Ching, Kevin; Lee, Joanna G.; Mauer, Elizabeth; Gerber, Linda M.; Sobin, Brittany; Osorio, Snezana Nena; DiPace, Jennifer I.
ABSTRACT: Interns and newly assigned nurses are expected to assimilate rapidly and begin functioning as members of interprofessional teams. This mixed-method pilot research assessed the impact of a Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS®) implementation plan in an urban academic teaching hospital that included a cohort of newly assigned pediatric interns and nurses (N = 23). We collected pre- and post-intervention course knowledge and team performance data from two teams in two separate simulation cases. We also surveyed the learners using an open-ended survey to ask about the value of their interprofessional learning experience. TeamSTEPPS® course knowledge improved from pre- to post-intervention (p < 0.001). Team performance scores were tallied and descriptively compared between pre- and post-intervention. Teams performed higher in both post-intervention simulation cases than in the pre-assessments. Post-intervention groups were assessed scores of 4 and 5 in more areas of the team performance checklist. Knowledge scores were compared between pre- and post- intervention by a Wilcoxon rank-sum test. Median scores improved from 17 to 20 following the intervention. Six themes emerged from the coding process that expressed a learned appreciation for contributing to a culture where the expectation is that team members speak up to support patient safety and other team members. As shown by this pilot research, TeamSTEPPS® training approaches that follow the 4-phase brain-based lesson plan for simulation and include interprofessional membership can be promising for integrating newly assigned members into existing clinical teams.